Extraction and separation of y-linolenic acid from lipids of Mortierella - Menor, Cecile C. (1987)
The cells of several species of the genus Mortierella were grown by fermentation and the fungal lipids were extracted with CHCL3/MeOH (2:1 v/v) and analyzed for their total, neutral and polar lipids composition by gas liquid chromatography. The main acids of the M. vinacea lipids are palmitic 27.30%, stearic 4.80%, oleic 45.40%, linolenic 12.98% and y- linolenic fatty acods 7.80%. A concentrate containing 97% of methyl y- linolenate was prepared from the subsequent urea complex separations of the non-adduct fractions of the fungal lipids.